(untitled) - Purba, Pincur Lamiduk; Triaryati, Nyoman (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p15, 2018)
Abstract The existence of OJK policy provides incentives to banks that can maintain NIM below 4%, without disrupting the bank's operations, be the background why then it is necessary to know any factors that affect the NIM. Net Interest Margin is the ratio of net interest income with the average earning assets. This ratio belongs to the bank profitability ratio and is one of the benchmarks of bank soundness. This study aims to examine several factors affecting NIM: Such as Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Income Operating Expense (BOPO), and Loan to Deposit Ratio (LDR) at commercial banks listed on the Stock Exchange Indonesia Securities (IDX) during 2012-2016. The number of samples taken as many as 31 companies with saturated sample method. The analysis technique used is multiple linear regression. The results showed that CAR and LDR had positive and significant effect on NIM, NPL had negative and significant effect on NIM, while BOPO had no significant effect on NIM   Key Words : NIM, CAR, NPL, BOPO, LDR.